POETRY AND POETIC CREATIVITY IN ALISHER NAVOI’S PERSIAN QIT’AS: ARTISTIC EXPRESSION AND LITERARY CRITERIA - Masutova Shakhlo Omonovna (International Journal of Literature and Language Studies, 2026)
This article analyzes Alisher Navoi’s views on poetry and poetic creativity as reflected in his Persian qit’as from the perspectives of artistic expression, literary criteria, and creative potential. The study considers poetry not only as an artistic activity but also as a system closely connected with ethical and social relations. Four samples from Navoi’s Persian qit’as were selected for analysis.